2009
DOI: 10.3749/canmin.47.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Greenockite and Associated Sulfide Mineralization From the Caledonia Group Mines, Blanca Creek, La Huerta Range, San Juan Province, Argentina

Abstract: We document various textural occurrences of greenockite associated with several ore minerals in varying parageneses: pyrite + sphalerite + galena + chalcopyrite ± arsenopyrite ± pyrrhotite ± bornite ± tennantite ± tetrahedrite ± covellite ± chalcocite ± aikinite ± wittichenite ± matildite ± berryite ± miharaite ± geocronite ± hematite ± magnetite from mineralized samples of the Caledonia Group mines, Marayes mining district, La Huerta Range, San Juan province, Argentina, based on reflected light and scanning e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…The Zn content varied (5.61 to 21.7 mol % ZnS), similarl to other occurrences of greenockite in hydrothermal deposits [4,11], e.g., 6-11 mol % ZnS in the Madjarovo Pb-Zn deposit [21], the maximum difference in different types of greenockite in the Caledonia Group being <1 to 25 mol % ZnS [11], and 42-59 mol % ZnS in the Tsumeb, southwest Africa [17]. In comparison to other occurrences, the zincian greenockite in the Saishitang deposit could be divided into two phases (I and II).…”
Section: Factors Influencing Composition Of Zincian Greenockitementioning
confidence: 78%
See 4 more Smart Citations
“…The Zn content varied (5.61 to 21.7 mol % ZnS), similarl to other occurrences of greenockite in hydrothermal deposits [4,11], e.g., 6-11 mol % ZnS in the Madjarovo Pb-Zn deposit [21], the maximum difference in different types of greenockite in the Caledonia Group being <1 to 25 mol % ZnS [11], and 42-59 mol % ZnS in the Tsumeb, southwest Africa [17]. In comparison to other occurrences, the zincian greenockite in the Saishitang deposit could be divided into two phases (I and II).…”
Section: Factors Influencing Composition Of Zincian Greenockitementioning
confidence: 78%
“…The EPMA data indicated that zincian greenockite contains 72.4-89.9 mol % CdS, which was in accordance with the experimental data of the ZnS-CdS system at 250 °C [7], and furthermore, the composition and structure were in line with the greenockite series [45] (cited in [2]). The Zn content varied (5.61 to 21.7 mol % ZnS), similarl to other occurrences of greenockite in hydrothermal deposits [4,11], e.g., 6-11 mol % ZnS in the Madjarovo Pb-Zn deposit [21], the maximum difference Figure 11. Compositions of cobaltite in the system of CoAsS-FeAsS-NiAsS, mol % (after [44]).…”
Section: Factors Influencing Composition Of Zincian Greenockitementioning
confidence: 79%
See 3 more Smart Citations